The impact of Fundamental Factors on Stock Return of The Engineering and Construction Services Company - Santoso, Bambang; Sidharta, Eka Ananta; Wardini, Amalia Kusuma (Jurnal Organisasi dan Manajemen, 2020)
This research was conducted to analyze the impact of selected fundamental factors on stock returns of Engineering and Construction Companies listed on the Indonesia Stock Exchange (IDX) using a quantitative approach. The research population includes all Engineering and Construction Companies listed on the IDX but 10 were selected as cross-section samples using a simple random sampling technique with criteria include being listed on the IDX and having time-series financial report data for 2015Q1 - 2019Q2 period. Data were retrieved from the companies’ audited financial statements and the independent variable which is stock return was determined using Panel Data and analyzed with Multiple Regressions. Meanwhile, the model specification test was produced using the Fixed Effect Model as the fit model. Findings. The results showed several fundamental factors of CR, NPM, PBV, EPS, and ROE partially has a significant positive effect on stock returns while DER has a significant negative effect and PER has a slightly positive influence. These findings are expected to contribute positively to the development of theories concerning the financial performance of stock returns. Moreover, the managerial implication of this research is that investors can use fundamentals analysis with a focus on CR, DER, EPS, NPM, PBV, PER, and ROE as the basis for decision making due to their influence on Stock Return.